Nanostructured capsules for cartilage tissue engineering - Correia, Clara R. (2015)
Polymeric multilayered capsules (PMCs) have found great applicability in bioencapsulation, an evolving branch of tissue engineering and regenerative medicine. Here, we describe the production of hierarchical PMCs composed by an external multilayered membrane by layer-by-layer assembly of poly(L-lysine), alginate, and chitosan. The core of the PMCs is liquified and encapsulates human adipose stem cells and surface functionalized collagen II-TGF-Î²3 poly(L-lactic acid) microparticles for cartilage tissue engineering.